An empirical study of tourist preferences using conjoint analysis - Shalini N. Tripathi; Masood H. Siddiqui (International Journal of Business Science & Applied Management (IJBSAM), 2010)
Tourism and hospitality have become key global economic activities as expectations with regard to our use of leisure time have evolved, attributing greater meaning to our free time. While the growth in tourism has been impressive, India's share in total global tourism arrivals and earnings is quite insignificant. It is an accepted fact that India has tremendous potential for development of tourism. This anomaly and the various underlying factors responsible for it are the focus of our study. The objective being determination of customer preferences for multi attribute hybrid services like tourism, so as to enable the state tourism board to deliver a desired combination of intrinsic attributes, helping it to create a sustainable competitive advantage, leading to greater customer satisfaction and positive word of mouth. Conjoint analysis has been used for this purpose, which estimates the structure of a consumer's preferences, given his/her overall evaluations of a set of alternatives that are pre-specified in terms of levels of different attributes.
Keywords: 650; Uttar Pradesh tourism; tourist preferences; conjoint analysis; binary logistic models